2014
DOI: 10.1027/1614-0001/a000130
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Negative Affect After Repeated Failure

Abstract: Perfectionists have shown increased negative affect after failure compared to nonperfectionists. However, little is known about how perfectionists react to repeated failure. This study investigated the effects of two forms of perfectionism – self-oriented perfectionism and socially prescribed perfectionism – on 100 university students’ reactions to repeated failure (versus repeated success) examining three negative emotions: anxiety, depression, and anger. Results showed that socially prescribed perfectionism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 29 publications
3
51
2
7
Order By: Relevance
“…Some studies have found that PC perfectionism is linked to higher levels of negative affect, and PS perfectionism is linked to lower levels of negative affect (e.g., Damian et al, 2014;Gaudreau & Thompson, 2010;Molnar et al, 2006), whereas other studies have found that only PC perfectionism, but not PS perfectionism is linked to state negative affect (e.g., Flett et al, 2009). When negative affect is construed as depression, anxiety, and anger (e.g., Hewitt & Flett, 2004;Stoeber, Schneider, Hussain, & Matthews, 2014), or as chronic negative emotionality (Shanmugasegaram et al, 2014), positive asso-ciations have been noted for both perfectionism dimensions, with stronger associations noted for PC perfectionism than PS perfectionism (e.g., Hewitt & Flett, 2004), especially after repeated failures .…”
Section: Perfectionism Affect and The Self-regulation Of Health Behmentioning
confidence: 99%
“…Some studies have found that PC perfectionism is linked to higher levels of negative affect, and PS perfectionism is linked to lower levels of negative affect (e.g., Damian et al, 2014;Gaudreau & Thompson, 2010;Molnar et al, 2006), whereas other studies have found that only PC perfectionism, but not PS perfectionism is linked to state negative affect (e.g., Flett et al, 2009). When negative affect is construed as depression, anxiety, and anger (e.g., Hewitt & Flett, 2004;Stoeber, Schneider, Hussain, & Matthews, 2014), or as chronic negative emotionality (Shanmugasegaram et al, 2014), positive asso-ciations have been noted for both perfectionism dimensions, with stronger associations noted for PC perfectionism than PS perfectionism (e.g., Hewitt & Flett, 2004), especially after repeated failures .…”
Section: Perfectionism Affect and The Self-regulation Of Health Behmentioning
confidence: 99%
“…Perfectionism is defined as a personality type where an individual (student) tries to be faultless and sets exceedingly higher goals regarding academic performance and overly critiques his or her behavior (Stoeber, Schneider, Hussain & Matthews, 2014). (Hewitt and Flett, 1991) operationalized perfectionism into these three components: self-oriented, other-oriented and socially-prescribed perfectionism.…”
Section: Antecedents Of Statistics Anxietymentioning
confidence: 99%
“…Indeed, the potentially adaptive effects of Perfectionistic Strivings (or its components) often are only uncovered once the joint variance between Perfectionistic Strivings and Perfectionistic Concerns has been statistically accounted for in the analyses (see Hill, Huelsman, & Araujo, 2010;Stoeber, Kobori, & Brown, 2014a). Some researchers suggest that it is important to test multiple dimensions of perfectionism simultaneously so that researchers can statistically control for the joint variance among the dimensions of perfectionism so as to "purify" the dimension of interest (Aldea & Rice, 2006;Stoeber, Schneider, Hussain, & Matthews, 2014b). These suppression effects have been replicated numerous times suggesting that they are not simply a statistical artefact that can be brushed under the proverbial carpet.…”
Section: Issue 4 Suppressionmentioning
confidence: 99%